Communicating in the agricultural industry - Graves, Russell A. (Thomson / Delmar Learning, 2005)
This book is meant to help bridge that gap. If agriculturists can communicate effectively about their industry, then everyone wins, and consumer confidence remains high. The book, however, is not meant to be the authority on communicating in the agricultural industry. Its purpose is to give you a reference point for further investigation into the discipline. The sections on writing should be supplemented with other books on writing, along with a good dose of practice. The same concept applies to the sections on speaking, photography, and graphic design. This book is your starting point to expand your knowledge of all these disciplines.